Fuzzy logic based model to measure knowledge sharing - Zadjabbari, Behrang; Mohseni, S.; Wongthongtham, Pornpit (IEEE, 2009)
Nowadays, trust is one of the most important variables in business. Lack of trust has a direct impact on business components confidence, trustworthiness can create value and leads business to obtain high market share. Trust is also the most important variable in knowledge sharing on the basis of the knowledge context. Different kinds of trust requires in knowledge sharing. Complexity and structured level of knowledge are the two important factors in knowledge classification. In this paper competence-based trust and benevolence-based trust will be discussed and knowledge sharing will be compared in different knowledge context and in different trust types. Effective knowledge sharing can be encouraged by improving the different types of trust. It is essential we discuss about trust definition and trust measurement in knowledge sharing.